Analisis Penerapan Sistem Antrian Model Multiple Channel Query System Atau M/M/S (Studi Kasus Pada PT Bank Rakyat Indonesia (Persero) Tbk Kanca Teluk Betung Bandar Lampung dan PT Bank Syariah Mandiri (BSM) Kcp Teluk Teluk Betung Bandar Lampung) - Iskandar Ali Alam; Penny Anggraini (Universitas Bandar Lampung (UBL), 2021)
PT Bank Rakyat Indonesia (Persero) Tbk Kanca Teluk Betung Bandar Lampung using a queuing system model of a multiple track or Multiple Channel Query System (M/M/S) with four person tellers. From the data processing, the highest number of customers waiting in the queue occurred in the period of 08.00-09.00 and 13.00-14.00 as many as 23.56 people with the longest average time spent by customers in the queue for 18.36 minutes. While the results of data processing using Multiple Channel Query System (M/M/S) model by increasing the number of tellers to five people, obtained the number of customers waiting in the queue occurred in the period of 08.00-09.00 and 13.00-14.00 as much as 1.67 people with time the longest average customer spent in the queue for 1.3 minutes. This shows that the performance of queuing system at counter teller of PT Bank Rakyat Indonesia (Persero) Tbk Kanca Teluk Betung Bandar Lampung will increase if adding one teller by using the same queue system that is Multiple Channel Query System (M/M/S). PT Bank Syariah Mandiri (BSM) Kcp Teluk Teluk Betung Bandar Lampung using a queuing system model of a single track or Single Channel Query System (M/M/1) with the number of one person teller. From the results of data processing, this model shows the highest number of customers waiting in the queue occurred in the period of 08:00 to 09:00, 10:00 to 11:00 and 13:00 to 14:00 as many as 19 people and the longest average time spent by customers in the queue for 60 minutes. From the results of data management using multiple track queuing system or Multiple Channel Query System (M/M/S), the number of customers waiting in the queue that occurred in the time period 08.00-09.00, 10.00-11.00 and 13.00-14.00 decreased by 17.77 person to 1.23 people and the longest average time spent by customers in the queue is reduced from 56.16 minutes to 0.87 minutes. This shows the performance of queuing system at PT Bank Syariah Mandiri counter (BSM) Kcp Teluk Teluk Betung Bandar Lampung will increase by using Multiple Channel Query System (M/M/S).